Evaluation of Curriculum Structure in Arts Education: A Systematic Literature Review at Elementary School Level - Maria Ulfa Yudha Julistiyana; Anik Ghufron; Primus Devra Raihan; Muhammad Fazli Taib Saearani; Adelina Luft (Universitas Muhammadiyah Mataram, 2025)
Arts education in elementary schools plays a vital role in shaping children’s character, creativity, and cultural identity. However, in Indonesia, its implementation faces challenges due to the fragmented organization of materials and the absence of standardized assessment frameworks. This study aims to identify dominant approaches to organizing arts curricula, evaluate relevant assessment models, and derive policy insights to strengthen primary school arts education. Using a Systematic Literature Review (SLR) of 30 peer-reviewed articles published between 2018 and 2024, selected from databases such as Scopus and ERIC, the analysis applied PRISMA guidelines and thematic coding to map key patterns. The review identified three main organizational approaches: Discipline-Based Art Education (DBAE), STEAM-PBL integration, and local wisdom-based methods. Among evaluation frameworks, the CIPP model emerged as the most comprehensive because it addresses outcomes along with context, input, and process. The findings show that each approach offers distinct strengths. DBAE provides a structured academic foundation, STEAM-PBL promotes creativity and critical thinking, and local wisdom methods reinforce cultural identity. Despite this, Indonesia’s curriculum lacks a cohesive and measurable framework that integrates these elements. This study provides conceptual insights to inform curriculum development and policy formulation, aligning arts education with global educational shifts and Indonesia’s cultural context.